2010
DOI: 10.1159/000306055
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Survival of Patients with Neurodegenerative Disease

Abstract: Background: Survival varies widely among different neurodegenerative diseases. Data on the role of the Mini Mental State Examination (MMSE) and apolipoprotein E (APOE) in survival are sparse except for Alzheimer’s disease (AD). Methods: We studied mortality of 3,581 patients in an academic clinic from 1993 to 2004. Average follow-up was 4.1 years. We studied patients with amyotrophic lateral sclerosis (ALS) (n = 174), possible AD (n = 206), probable AD (n = 1,175), Parkinson’s disease (PD) (n = 661), mild cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 94 publications
(54 reference statements)
7
39
1
3
Order By: Relevance
“…Seven studies found that VaD had a worse prognosis than AD, whereas two studies found AD to have a worse prognosis than VaD [4]. Furthermore, previous findings have observed a higher mortality for FTD patients compared to AD patients [44]. In the present study, we observed that patients with FTD had a SMR of 0.24, which was significantly different from the SMR of patients with AD (0.34).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Seven studies found that VaD had a worse prognosis than AD, whereas two studies found AD to have a worse prognosis than VaD [4]. Furthermore, previous findings have observed a higher mortality for FTD patients compared to AD patients [44]. In the present study, we observed that patients with FTD had a SMR of 0.24, which was significantly different from the SMR of patients with AD (0.34).…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, Guehne et al [6] found an increased risk of death, about 1.5 times higher in patients with MCI, when certain diagnostic criteria are applied. Likewise, Steenland et al [44] have shown that the mortality of MCI patients is 50–100% higher than the mortality of controls. In the present study, patients with MCI showed an increased mortality with an SMR of 0.34.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have found consistent evidence of an approximately 20% longer survival after AD diagnosis for AAs versus CCs [14, 34, 41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…It is the second most common form of neurodegenerative dementia after Alzheimer's disease (AD), but reported frequencies vary from 0-25% [1,2]. It has been found that patients with DLB have higher mortality [3,4], have shorter time until nursing home admission [5], use more resources [6] and perform worse in activities of daily living. There is also higher overall caregiver stress compared with AD [7,8].…”
Section: Introductionmentioning
confidence: 99%